1D flower-like Fe3O4@SiO2@MnO2 nanochains inducing RGO self-assembly into aerogels for high-efficient microwave absorption. (March 2020) - Ma, Mingliang; Li, Wenting; Tong, Zhouyu; Yang, Yuying; Ma, Yong; Cui, Zhonghe; Wang, Rongzhen; Lyu, Ping; Huang, Weibo
Abstract: One-dimensional (1D) microwave absorbing materials (MAMs) can induce self-assembly of graphene into aerogels, which provides ideas for the preparation of new MAMs. In here, 3D flower-like Fe3 O4 @SiO2 @MnO2 @reduced graphene oxide (RGO) (FSMG) composite aerogels have been fabricated via hydrothermal method, in which 1D Fe3 O4 @SiO2 (FS) nanochains and two-dimensional (2D) MnO2 sheets form a nano-scale core-shell structure on the surface of the RGO nanosheets. The unique microstructure of aerogels greatly enhances the microwave absorption capability. Particularly, the addition of RGO regulates the complex permittivity and improves the impedance matching of 1D Fe3 O4 @SiO2 @MnO2 (FSM) nanochains. Results demonstrate that the well-designed 3D conductive networks with significant oxygen vacancy defects powerfully favor the electromagnetic wave (EMW) absorption. The as-prepared FSMG composite aerogels show efficient microwave absorption (MA) properties with the maximum effective absorption bandwidth (EAB) of 4.26 GHz (7.13–11.39 GHz) at the corresponding coating thickness of 3.2 mm, accompanied by the minimum reflection loss (RLmin ) of about −55.01 dB. This work indicates that the FSMG composite aerogels are excellent absorbers with wide bandwidth, strong absorption, thin thickness and light weight, which can become a hopeful candidate in the field of MA. Graphical abstract: Unlabelled Image Highlights: The novel lightweight composite aerogels of Fe3 O4 @SiO2 @MnO2 @RGO were fabricated successfully. One-dimensional flower-like Fe3 O4 @SiO2 @MnO2 nanochains were uniformly anchored onto the surface of the RGO nanosheets. The microwave absorption mechanism of Fe3 O4 @SiO2 @MnO2 @RGO composite aerogels was elucidated in depth. The composite aerogels exhibit strong absorption (RLmin  = −55.01 dB at 7.78 GHz) and broad bandwidth (7.13–11.39 GHz).